Two decades of echinococcosis/hydatidosis research: Bibliometric analysis based on the web of science core collection databases (2000–2019) - Fakhar, Mahdi; Keighobadi, Masoud; Hezarjaribi, Hajar Ziaei; Montazeri, Mahbobeh; Banimostafavi, Elham S.; Sayyadi, Shahram; Ghaffari Hamadani, Mohammad M.; Sharifpour, Ali; Tabaripour, Rabeeh; Asadi, Samira; Soosaraei, Masoud; Khasseh, Ali A. (Food and waterborne parasitology, 2021)
Echinococcus granulosus sensu lato and Echinococcus multilocularis are responsible for serious health and economic implications for humans and animals. This study was designed to conduct a bibliometric analysis of global research on echinococcosis/hydatidosis included in the Web of Science Core Collection databases from 2000 to 2019. A total of 7066 relevant articles between 2000 and 2019 were identified. Most articles were published in 2015 (502 articles), 2017 (492 articles) and 2018 (493 articles), with the Veterinary Parasitology journal publishing the largest number of articles (237). Researchers from Xinjiang Medical University, China authored the most articles (388) in the field. Authors Craig, P.S. and Deplazes, P. were the most active in publishing143 and 126 hydatid cyst research papers, respectively. The most echinococcosis/hydatidosis publications originated from Turkey, China and Iran, with 1210, 708 and 531 articles, respectively. The highest levels of research collaboration were evident between China- England, China-France, England-France, China-Australia, and China-Japan. Also, the top researchers in this field had relatively extensive collaborations with each other. Our bibliometric analysis provides a picture of the scientific research into the echinococcosis/hydatidosis field. Further multi-national collaborative research efforts in this field should show promising progress in the future.